Daidzein Hydroxylation by CYP81E63 Is Involved in the Biosynthesis of Miroestrol in Pueraria mirifica. (11th October 2022) - Suntichaikamolkul, Nithiwat; Akashi, Tomoyoshi; Mahalapbutr, Panupong; Sanachai, Kamonpan; Rungrotmongkol, Thanyada; Bassard, Jean-Etienne; Schaller, Hubert; De-Eknamkul, Wanchai; Vimolmangkang, Sornkanok; Yamazaki, Mami; Sirikantaramas, Supaart
Abstract: White Kwao Krua ( Pueraria candollei var. mirifica ), a Thai medicinal plant, is a rich source of phytoestrogens, especially isoflavonoids and chromenes. These phytoestrogens are well known; however, their biosynthetic genes remain largely uncharacterized. Cytochrome P450 (P450) is a large protein family that plays a crucial role in the biosynthesis of various compounds in plants, including phytoestrogens. Thus, we focused on P450s involved in the isoflavone hydroxylation that potentially participates in the biosynthesis of miroestrol. Three candidate P450s were isolated from the transcriptome libraries by considering the phylogenetic and expression data of each tissue of P. mirifica . The candidate P450s were functionally characterized both in vitro and in planta. Accordingly, the yeast microsome harboring PmCYP81E63 regiospecifically exhibited either 2′ or 3′ daidzein hydroxylation and genistein hydroxylation. Based on in silico calculation, PmCYP81E63 had higher binding energy with daidzein than with genistein, which supported the in vitro result of the isoflavone specificity. To confirm in planta function, the candidate P450s were then transiently co-expressed with isoflavone-related genes in Nicotiana benthamiana . Despite no daidzein in the infiltrated N. benthamiana leaves, genistein and hydroxygenistein biosynthesis were detectable by liquid Chromatography with tandem mass spectrometry (LC-MS/MS). Additionally, we demonstrated that PmCYP81E63 interacted with several enzymes related to isoflavone biosynthesis using bimolecular fluorescence complementation studies and a yeast two-hybrid analysis, suggesting a scheme of metabolon formation in the pathway. Our findings provide compelling evidence regarding the involvement of PmCYP81E63 in the early step of the proposed miroestrol biosynthesis in P. mirifica .